Reducing Salt Intake and Exercising Regularly: Implications From Molecular Dynamics Simulations of Endothelial Glycocalyx - Jiang, Xi Zhuo; Luo, Kai H.; Ventikos, Yiannis (Frontiers in Physiology, 2018)
It is widely accepted that salt intake reduction and regular exercise is a healthy lifestyle, which can prevent cardiovascular diseases (CVD). Meanwhile, there is evidence that the endothelial glycocalyx layer (EGL) is related to CVD. However, how such a healthy lifestyle helps to prevent CVD via the function of the EGL has not been scientifically established. In this research, a series of large-scale molecular dynamics simulations have been conducted to study ion transport inside the endothelial glycocalyx layer under varying flow velocities. Results show that a fast blood flow velocity favors the Na+ transport out of the EGL, which can explain the increase in the thickness of an exclusion layer between red blood cells and the EGL under fast blood flow situations, as witnessed in some previous experiments. Based on findings from this fundamental research, a theory is proposed, which can answer the open-ended question “Why do we need to reduce salt intake and exercise regularly” . The findings may also have implications for other therapies to combat cardiovascular diseases.